واقع إعداد معلم التعليم الثانوي في بعض كليات التربية بالجامعات السودانية (Journal of Faculty of Education, 2021)
The study aims at identifying the current situation of secondary school teachers' training (preparation) programs in some faculties of education in universities in Sudan. Emphasis will be on the scrutiny and evaluation of the objectives of training (preparation) programs and how they contribute to the development of academic, educational and cultural capabilities of teachers. The study also attempts to identify the difficulties associated with these training programs.The study adopted the descriptive method. A questionnaire was used to collect the data. The population of the study was composed of fourth year students in faculties of education of the universities of Khartoum, ALazhary, Kordofan and West Kordofan from which a random sample of 248 students was chosen.The most important results are; the objectives of secondary school teacher training programs in the faculties of education under question were similar; there was a maked absence of strategic objectives and clear standards for designing teachers’ training programs; The number of Credit Hours devoted for education subjects is different from one faculty to another. Cultural Programs are poor and,more, the programs do not provide the student teachers with adequate language skills which can help him/ her in teaching . Further,the programs of the `content of the academic subjects of specialization are not regularily up- dated and improved. There are, also, difficulties facing teachers' training programs in the examined faculties such as absence of clear standards for designing programs, absence of the integration between theory and practice, poor evaluation and assessment methods, lack of Laboratories and multi-media centers, poor libraries, lack of basic references, unfavourable lecture rooms conditions and absence of academic supervision of the students. Pushed by these results, In light of these results, the study recommended that the notion of student and regional and environmental diversity should be taken into consideration when designing the aims of faculty programs and the services these faculties provides to society. In addition, the Credit Hours devoted to cultural, educational and academic programs should be similar among all faculties of Eeucation.
Keywords: معلم التعليم الثانوي; كليات التربية بالجامعات